A General Survey of Nitrate-Nitrogen Levels In Well-water under Different Landuses - Yusoff, Khatijah; Sulaiman, Wan Nor Azmin; Sharif, Zainudin (1990)
A general survey on N03 - - N levels in well-water under different landuses was conducted. Four areas were selected to represent different landuses namely mixedfarming (crop and animal production), forest, urban, and crop production only. Water samples from a total of 22 wells in the selected areas were collected and analysedfor N03- - N. The field and statistical data showed that the differences in N03 - - N levels in well- waterfrom different landuses were significant except for agriculture + animal farming. The highest N03 - - N level was observed in agricultural areas followed by urban and forested areas.